GĀ NMA KE KANEMQ SISIDSE WOLO - J. G. Chr. (Evangelical Missionary Society. Basel Mission Book Depot, Christiansborg, Gold Coast, 1892)
This document is a Ga language primer, originally compiled in the 1860s and revised in the 1880s, with this specific reprint issued in 1892. Its primary purpose is to teach literacy in Ga (also referred to as Akra) to children and learners on the Gold Coast (modern-day Ghana). The book begins with detailed instructions for teachers on pedagogical methods, emphasizing writing practice, syllable recognition, and dictation. A significant portion of the introduction is dedicated to explaining the Ga alphabet based on Lepsius's Standard Alphabet, its pronunciation, and the language's complex tonal system, providing rules for using accents to denote high, low, and middle tones. The core of the primer consists of extensive reading and writing exercises, starting from basic syllables and progressing to complex words and sentences. It includes vocabulary lists categorized by theme (e.g., body parts, family relations, household items) and grammatical function (nouns and verbs arranged by their tonal patterns). Later sections incorporate religious and moral instruction, featuring Biblical passages, hymns, names of Biblical figures, and parables. The document also contains practical sections on numeracy, including multiplication tables, and concludes with longer reading passages and stories designed to reinforce language comprehension. Overall, it serves as a comprehensive educational tool, reflecting the linguistic and evangelical efforts of the Basel Mission in late 19th-century West Africa
PRIMER IN THE GĀ OR AKRA LANGUAGE, GOLD COAST, W. AFRICA.
Keywords: Ga Language; Primer; Literacy; Gold Coast; Basel Mission